Relacje z rówieśnikami i ich znaczenie dla młodzieży z umiarkowanym i znacznym stopniem niepełnosprawności intelektualnej w edukacji specjalnej – w świetle badań własnych - Drozdowicz, Anna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The article presents a summary of the research about peer relationships among the young with intellectual disability in special education classes. The studies took into consideration a) the types of the relationships and their qualitative characteristics, b) factors determining the type of the relationship, c) an individual perspective of a young disabled person in the group of mentally disabled peers.71 pupils with moderate and severe intellectual disability in 15 special education classes were observed in natural school situations. The results show a great need and abilities to participate in peer relationships by intellectually disabled teenagers. The second part of the study was based on the qualitative research procedure and revealed different subjective meaning of participation of 7 young intellectually disabled students in the school peer group. Findings of the study gave practical indications for arranging special classes of pupils with moderate and severe intellectual disability. Results was discussed with current tendency to inclusive education people with disability.